The effect of passage through the gut of the Greater Rhea (Rhea americana) on germination of tree seeds: Implications for forest restoration - Renison, Daniel (2010)
Long-distance dispersal of seeds is an important process for maintaining genetic connectivity between forest fragments and for promoting fast re-colonisation of deforested land. Based on the hypothesis that the Greater Rhea (Rhea americana), a large flightless bird native to South America, could play a major role as a disperser of tree seeds, we evaluated whether passage of seeds through its digestive tract affected germination of six tree species native to central Argentina. We determined the proportion of seeds that germinated in a climate-controlled chamber for untreated (control) seeds, as found under seeding trees, seeds that passed through the digestive tract of captive Greater Rheas, and seeds treated with optimum pre-germination treatments for seedling production. Our results showed that the germination response to passage through the gut reached or surpassed the optimum germination treatments in three species of tree, was similar to control treatments and lower than optimum treatments in two species, and lower than all alternative treatments in one species of tree. We conclude that Greater Rheas are one of the few remaining large-bodied native animals with potential to disperse seeds of large fruits effectively, thus reinforcing the importance of restoring former populations of Greater Rhea. © 2010 Royal Australasian Ornithologists Union.